Reviews : A day in the life. (10th January 2018) - Rao, Achintya
Abstract: Even the most avid physics enthusiast does not necessarily awaken each morning and turn their mind to the various physical processes they will encounter over the course of their day. Yet this is precisely the sort of journey that author James Kakalios takes us on in his book The Physics of Everyday Things .